THE ASSESMENT OF HISTORY LEARNING IN IMPLEMENTATION OF KURIKULUM MERDEKA - Armiyati, Laely; Agung, Leo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
History learning includes three activities, namely planning, implementation and assessment. However, history teachers tend to be more concerned with planning and implementation, while the assessment aspect is considered less important. In the Kurikulum Merdeka, assessment is an activity that is as important as learning, even the official guidelines are entitled